Off-label use of IV t-PA in patients with intracranial neoplasm and cavernoma - Schwarzbach, Christopher Jan; Ebert, Anne; Hennerici, Michael G.; Neumaier-Probst, Eva; Platten, Michael; Fatar, Marc (Therapeutic advances in neurological disorders, 2018)
Background:The safety of systemic thrombolysis in patients with intracranial tumor and cavernoma are unknown. So far evidence is limited to a number of case reports and few case series or unspecified data based on population-based analysis. Our aim was to comprehend the risk of systemic thrombolysis in these patients.Methods:Patients with additional evidence of intracranial tumor or cavernoma who received IV tissue plasminogen activator (t-PA) treatment at our comprehensive stroke center over a period of 7 years were identified in our stroke database and compared to the same number of matched control subjects without any evidence of intracranial tumor and cavernoma. Clinical history and imaging patterns before and after t-PA therapy were individually reviewed for each patient.Results:Thirty-four patients with additional evidence of meningioma (19/34), cavernoma (13/34) or malignant intracranial neoplasm (2/34) were identified. The incidence of secondary intracranial hemorrhage observed showed no difference between control subjects (9/34, 26%) and patients (6/34, 18%; p = 0.56). Symptomatic hemorrhage in patients with meningioma or cavernoma could not be observed. Likewise, the prevalence of stroke mimics showed no difference between patients (8/34, 24%) and control subjects (5/34, 15%; p = 0.54). However, both patients with malignant intracranial neoplasm presented with a stroke mimic and intracranial hemorrhage was observed in one of them.Conclusions:In compliance with existing evidence, treatment in patients with meningioma and cavernoma appears to be safe and reasonable, while the therapy should be avoided in patients with malignant intracranial neoplasm with blood?brain barrier disruption.